2016
DOI: 10.1002/tesj.245
|View full text |Cite
|
Sign up to set email alerts
|

Elementary EFL Students' Practice of Peer Assessment of Oral Classroom Activities

Abstract: Role-play is an oral classroom activity that has been promoted to provide young learners with opportunities to practice English in meaningful contexts. To familiarize elementary students with this group task, to encourage them to pay attention to their peers' performances, and to replace traditional paper-and-pencil modes of evaluating speaking tasks, an alternative group peer assessment (PA) was proposed in this action research implemented with 114 fourth-grade and fifth-grade students in four classes in an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…The findings corroborate the ideas of previous studies (e.g. Gielen and De Wever, 2015;Hung et al, 2016), in which peer feedback exerts positive impacts on student engagement in learning and practising their speaking skills. Moreover, the shared visions and collaborative relationships enhance active student engagement in provoking lively discussions in which they will learn from each other.…”
Section: Discussionsupporting
confidence: 90%
“…The findings corroborate the ideas of previous studies (e.g. Gielen and De Wever, 2015;Hung et al, 2016), in which peer feedback exerts positive impacts on student engagement in learning and practising their speaking skills. Moreover, the shared visions and collaborative relationships enhance active student engagement in provoking lively discussions in which they will learn from each other.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, to some extent, it can be claimed that pencil tests may not judge students' overall knowledge and information for their regular improvement of learning. Hung et al (2016) suggested involving students in peer assessment (PA) to assess the speaking performance of students and their study further suggests "needs awareness, scaffolding instruction, and proper training" (p. 465) for the PA classroom. This also suggests that there is a need for alternative assessments which might judge students' overall quality through continuous evaluation/formative assessment so that regular improvement is possible for a continuous learning process.…”
Section: Examination As a Phobiamentioning
confidence: 99%
“…Bennett, Parker, & Smigiel, 2012), and encourage students' participation (e.g. Hung, Chen, & Samuelson, 2016). The interplay between group size, students' participation and performance in peer assessment is seemingly not well understood.…”
Section: Optimal Group Size In Peer Assessmentmentioning
confidence: 99%